Análisis del impacto económico y financiero que han tenido las entidades sin ánimo de lucro dedicadas al sector cultural en la ciudad de Cúcuta a raíz de la pandemia covid-19 (2022)
The present work of degree, analyzes the economic and financial impact that have had the non-profit entities dedicated to the Cultural Sector in the city of Cucuta as a result of the Pandemic Covid-19, showing the application of the descriptive methodology using field research resources and characterization surveys; in fact, the financial situation is analyzed and the new behaviors for the sector in question, in the different components that give rise to the financial statements, achieving as a result the determination of the effects that occurred the administration of the working capital.